Leukocyte Differential Study in Wild Hawksbill Turtles (Eretmochelys imbricata) - Zulfikar Basrul; Septiadi Yusuf Sulaiman; Nabillah Azzah; Rozalinda; Nur Azisya; Nurdin, Muhammad Ardiansyah; Anshar, Amelia Ramadhani (Hasanuddin University, 2024)
Wild hawksbill turtles (Eretmochelys imbricata) can be affected by various diseases which generally affect disorders to respiratory system, digestive system, metabolic system, bones, skin and reproductive system. As a diagnose confirm to the disease is through blood tests, such as leukocyte differentiation calculations. Leukocytes are one of the blood cells that has main function of protecting the body from pathogen attack. Leukocytes consist of neutrophils, eosinophils, basophils, monocytes and lymphocytes. The purpose of this study was to provide information about leukocyte levels in wild hawksbill turtles (Eretmochelys imbricata) on Liukang Loe Island, Bulukumba Regency. The method used in turtle sampling is random sampling. Blood samples were taken from the supravertebral sinus (dorsal cervical vein) on the neck using a syringe. Then make preparations by adding methanol and then staining using Giemsa solution. The preparations were observed under a microscope with 40x magnification. Then do the calculation of each type of leukocyte to reach the number of 100 leukocyte cells. The results of observations obtained in one hawksbill turtle were 78 lymphocytes, 22 monocytes, 195 neutrophils, 3 eosinophils and 2 basophils. In the second hawksbill, 50 lymphocytes, 56 monocytes, 64 neutrophils, 2 eosinophils and no basophils. The differentiation results obtained in the hawksbill one were lymphocytes with a percentage of 26%, monocytes 7.3%, neutrophils 65%, eosinophils 1% and basophils with a percentage of 0.6%. In hawksbill turtles, two percentages were obtained, namely 16.6% lymphocytes, 18.6% monocytes, 64% neutrophils, 0.65% eosinophils and no basophils. Keywords : Eretmochelys imbricata, Leukocytes, Wild hawksbill turtle, Liukang Loe Island